Effects of Compost, Fertilization, Rhizobacteria and Mycorrhiza Applications on Growth, Flowering and Bulb Quality of ‘Jan van Nes’ Tulip Varieties - Onur Sefa Alkaç; Mehmet Güneş (Turkish Journal of Agriculture: Food Science and Technology)
Compost is usually made of biodegradable wastes. Today, compost, bio-agent bacteria and mycorrhizae are used as the key components of sustainable agriculture. This study was conducted to determine the effects of compost treatments alone and combined with bacteria, mycorrhiza and commercial fertilizers on growth, flower and bulb quality parameters of the ‘Jan van Nes’ tulip cultivar. Compost was made of grape pomace and set at different EC levels. Three different compost ratios (0%, 20% and 40%), three different EC levels (0.75, 1.10, and 1.45 dS/m) and combinations with or without bacteria and mycorrhizae were experimented. Flower stalk length, perianth length and vase life were identified as the most striking parameters for growth and flowering of tulip plants. The best outcomes in terms of flower stem length (34.20 cm), perianth length (44.85 mm) and vase life (7.00 days) were obtained from 0% compost treatments. Increasing compost ratios had adverse effects on plant growth and bacteria and mycorrhizae treatments alone did not provide any significant effects. However, combining with different compost ratios increased the effectiveness of bacteria and mycorrhiza. EC of 0.75 yielded better results than the other EC levels.